Pedro Zulen, a revolutionary philosopher - Gonzales Alvarado, Osmar (2018)
In this article, the author makes reference to the intellectual figure which the philosopher Pedro Zulen represents in the Peruvian intellectual process within the social, cultural and political dynamic context which the Peruvian society experienced in the first decades of the XXth century, critical times of renewal of national life. For that, the author explores Zulen’s ideas and relates him with other important thinkers of his times.